An Assessment of the Impact of the National Commission on Higher Education Quality Assurance Policy for Tertiary Institutions in Liberia - S. Taylor, Momo; L.S. Nabieu, Paul (Sekolah Tinggi Ekonomi Syariah Manna Wa Salwa Tanah Datar Sumatera Barat, 2024)
This study looks at how Lofa County University in Liberia is affected by the NCHE quality assurance strategy. It examines the policy's application, the university's attempts to adhere to quality standards, and the difficulties encountered. Data was gathered and analyzed using a mixed method approach that combined quantitative and qualitative research techniques. The results indicate that LCU has endeavored to adhere to the NCHE quality assurance policy by employing skilled personnel, enhancing infrastructure, and pursuing program sustainability. The policy's execution has resulted in LCU obtaining accreditation to offer bachelor's degree programs and has enhanced program quality via consistent curricula and qualified personnel. Nevertheless, obstacles such as insufficient competent personnel and financial resources have been faced. The report concluded that the policy has positively impacted accreditation, personnel quality, infrastructure development, and program quality enhancement. The government of Liberia should augment financing for NCHE and LCU to guarantee adherence to quality assurance requirements.